Self-Selection Patterns In Mexico-U.S. Migration : the Role of Migration Networks - McKenzie, David J. (The World Bank, 2007)
The authors examine the role of migration networks in determining self-selection patterns of Mexico-U.S. migration. They first present a simple theoretical framework showing how such networks impact on migration incentives at different education levels and, consequently, how they are likely to affect the expected skill composition of migration. Using survey data from Mexico, the authors then show that the probability of migration is increasing with education in communities with low migrant networks, but decreasing with education in communities with high migrant networks. This is consistent with positive self-selection of migrants being driven by high migration costs, and with negative self-selection of migrants being driven by lower returns to education in the U.S. than in Mexico